Designing a Smart Drug Box - Javed, Ravish; Altaf, Meteb; AlQahtani, Mahdi; Altinawi, Amir; Alotaibi, Hassan; Almejrad, Saleh; Alswileh, Meshal (European Journal of Applied Sciences, 2021)
It is evident that punctuality in taking medicine can be an issue and failure to take appropriate medication as prescribed by the physician on the proper time may lead to health complications. Management of medication is very important for acute illness and long-term health conditions. Smart Drug Box (SDB) connected through a mobile application installed on the patient smartphone can be used to remind the patient as per the prescription by the physician. The construction of the SDB is divided into three phases. The first phase is the box design using Computer Aided-Design (CAD), the second phase is the software design, and the last phase is printing the box. The prototype of our SDB is designed with a miniaturized size and a user friendly-interface. The SDB prototype weighs 350 grams when empty without any medication. This SDB meets the needs of the market in terms of integrating electronic technology and network functionality and can be used by patients at their homes or by nursing facilities. Using the SDB will not only significantly reduce the chances of errors but also enhance and speed up the caretaker follow-up by letting the SDB to take care of medicine management. The proposed SDB is simple to use, affordable and, has high accuracy. The main purpose of this is to improve health care and patient’s overall health condition by giving scheduled reminders, therefore, ensuring patient adherence to the treatment plan in terms of dose time and quantity.